Sequence polymorphisms in the apolipoprotein (a) gene. Evidence for dissociation between apolipoprotein(a) size and plasma lipoprotein(a) levels. - Cohen, J C (1993)
Apolipoprotein(a) [apo(a)], an apolipoprotein unique to lipoprotein(a) [Lp(a)], is highly polymorphic in size. Previous studies have indicated that the size of the apo(a) gene tends to be inversely correlated with the plasma level of Lp(a). However, several exceptions to this general trend have been identified. Individuals with apo(a) alleles of identical size do not always have similar plasma concentrations of Lp(a). To determine if these differences in plasma Lp(a) concentrations were due to sequence variations in the apo(a) gene, we examined the sequences of apo(a) alleles in 23 individuals homozygous for same-sized apo(a) alleles. We identified four single-strand DNA conformation polymorphisms (SSCPs) in the apo(a) gene. Of the 23 homozygotes, 21 (91%) were heterozygous for at least one of the SSCPs. Analysis of a family in which a parent was homozygous for the same-sized apo(a) allele revealed that each allele, though identical size, segregated with different plasma concentrations of Lp(a). These studies indicate that the apo(a) gene is even more polymorphic in sequence than was previously appreciated, and that sequence variations at the apo(a) locus, other than the number of kringle 4 repeats, contribute to the plasma concentration of Lp(a).